Reliability and Validity of the Korean Version of Belongingness Scale-Clinical Placement Experience - Miyoung Kim, RN, PhD, MBA; Dukyoo Jung, RN, PhD (Elsevier, 2012)
Purpose: The purpose of this cross-sectional survey was to determine the reliability and validity of the Korean version of the Belongingness Scale-Clinical Placement Experience (BS-CPE). Methods: The study conducted a cross-sectional survey which used a self-report questionnaire. A convenient sampling method was utilized, and data on 335 students was gathered. We verified construct validity by performing confirmatory factor analysis. Results: The overall Cronbach's alpha score was .90 (range: .71-.84). BS-CPE was correlated with self-respect (r = .47, p < .001) and self-directed learning (r = .50, p < .001). The original BS-CPE was modified based on the validity test. Conclusion: This modified Korean version of the BS-CPE is applicable for use with university undergraduates to measure belongingness in clinical practice.